2021
DOI: 10.34190/ejbrm.19.2.2513
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Research Methods and the Supervision of Undergraduate Projects: Seeking Practical Improvements to a Complex Process

Abstract: This paper develops a review of teaching research methods and student supervisor relationships, first presented to ECRM20. Last year we tested an extensive literature review with a survey of undergraduate business students, this has now been supplemented with further survey data, interviews and a focus group.  This supplementary data has deepened our understanding of the issues and has largely reinforced the findings from the previous paper. At a time when some schools are moving content on-line and seeking ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Linking the goals to the necessary time, engagement and resources provided a reliable framework for the MT process. Providing and maintaining this framework is an important competency that supervisors should develop (or should be trained for) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Linking the goals to the necessary time, engagement and resources provided a reliable framework for the MT process. Providing and maintaining this framework is an important competency that supervisors should develop (or should be trained for) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most supervisors aimed to guide students towards increasing independence during the project, which is regarded a powerful driver for learning [ 35 ]. However, shaping this process of gradually and effectively fading out also calls for specific supervisor training [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, our experience of teaching research methods and supervising students in preparing dissertations has revealed a wide range of ability, enthusiasm and interest. More recently a growing level of disinterest in undertaking a project and learning research skills has become apparent (Brown and Rich, 2020;Mitchell andRich, 2020, Mitchell andRich, 2021). The popularity and recent growth in eBusiness may mean that assumptions underpinning a traditional Business School curriculum cease or are at least challenged.…”
Section: Introduction 11 Why Do Students Find It a Challenge?mentioning
confidence: 99%